Peruvian nursing and the COVID-19 pandemic: A fight against deliberate disinformation and the management of the vaccination process, 2020-2021 - Álvarez Vicente, Katerin Patricia (2022)
The contribution of nursing in Peru has been of vital importance in the fight against COVID-19. Starting from this premise, the objective of this research is to analyze the role played by nursing staff in hospital centers for the benefit of public health during the pandemic and the state of health emergency. The study is developed using the qualitative method, for which the information discourses published in the main newspapers are analyzed. The nurses who worked in the midst of the COVID-19 pandemic were the main actors in the containment to combat the deadly virus. Therefore, their participation in the vaccination campaigns undertaken was one of the highest expressions of commitment to the health welfare of Peruvian society. In order to achieve the defined goals of nursing in this conjunctural process, not only were the skills acquired sufficient, but it was also necessary to fight against the misinformation of the so-called anti-vaccine movements and the deficiencies of a collapsed health system. In this way, much of the success achieved by nursing was due to its own management and organization as committed professionals.